Trade Linkages and the Trade Matrices in the OECD Interlink Model - Le Fouler, Laurence (OECD Economics Department Working Papers, 2001)
This paper provides a mainly graphical summary of the trade matrices underlying the OECD's international macroeconomic model Interlink. In doing so it gives a snapshot of the geographical nature of global trading relationships, in particular between individual OECD countries and the main non-OECD regions, distinguishing trade in manufactures non-manufactures and non-factor services. It also serves more broadly as a 'ready reckoner' guide to the sensitivity of shocks that are transmitted through trade. The sources and methods used to construct the matrices are also described in annexes ...